If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2y = 6x Solving 4 + -2y = 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2y = -4 + 6x Combine like terms: 4 + -4 = 0 0 + -2y = -4 + 6x -2y = -4 + 6x Divide each side by '-2'. y = 2 + -3x Simplifying y = 2 + -3x
| sinx=2cosx | | 7x+8-9(x-1)=3x+2 | | -32+9+m=-6+12 | | 384/2304= | | 3xy+3y=7 | | 0.2x+2.7x=7.7-1.5+2.7x | | 20+x^2+9x=0 | | 2u^2-5u-16=u^2+4 | | f(x)=6x^4+23x^3+19x^2-8x-4 | | 192=1/212b | | 9+8x=23+x | | 2(3-5x)=3(3x+4) | | x-17+x=126 | | X^2+4x+22=-5x+2 | | 5(-4x+3)=10x-2 | | x+4.8=-6.7 | | 8x^3+4x^2+7x-1=0 | | 20(x)+7.5(x)=300 | | 87+95=j | | -35+x^2+-2x=0 | | 36x^4-36x^3+24x^2+9x+6=0 | | n^2+n-20= | | 2600000=.0000113x^3-.000922x^2+.0538x | | 4x-7+2x=2(3x-3) | | -8-3q=25 | | X^2-2x-29=6 | | -3(7x-2)+8x= | | 0.6%*x=7.5 | | 5x^2+2x=8 | | 10y=x^3 | | 8+x^2+-6x=0 | | s^3-st^2+s^2t-t^3= |